Evaluating Alternatives on Loss Production Opportunity Due to Surface Facility Constraint: Case Study of Anoa & Pesut Gathering Station in PT RCI (The Indonesian Journal of Business Administration, 2021)
Having managed one of the largest oil and gas concession in Indonesia for more than 90 years, PT RCI strives to optimize the highest recovery from Romeo block, including from Pesut field and its surrounding. As the asset matures and facility ages, the volume of unrealized production grows caused by reservoir dynamics and changes in environmental policy. The unrealized production volume per year is estimated at 40,000 bbls of oil. As the unrealized oil production inflicts revenue deferment and considering concession contract is near to its end, a list of potential alternatives was assessed to solved the problem. A team of experts are assembled to identify the fundamental problem through root cause analysis as well as generating potential recommendations. Using Value Focused Thinking (VFT) approach, experts discussed and identified the key value that the project want to achieve, then continued to identify opportunity to meet the criteria agreed. A multi criteria decision-making approach is carried out to carefully determine the best alternatives to minimize the unrealized oil production using Analytical Hierarchy Process (AHP). The decision-making process was guided using the combination of quantitative and qualitative criteria including safety aspect, perceived reliability and forecasted financial performance. The result suggested that simple facility alteration by creating interconnection pipe between two gathering stations as the most favored alternatives, providing highest short-term NPV coupled with high system reliability and manageable safety aspect. The proposed alternative is expected to recover 41,000 bbls of unrealized production until the end of concession, while add contractor’s net present value (NPV) of $23,785 with 1.6 of profitability index. Keyword: AHP (Analytical Hierarchy Process), VFT (Value Focused Thinking), LPO (Loss Production Opportunity)